Ensino de Matemática e Transtorno do Espectro Autista – TEA: possibilidades para a prática pedagógica nos anos iniciais do Ensino Fundamental - Santos, Josely Alves dos (2020)
This research started from the question: What are the possibilities for the development of the pedagogical practice of teachers who teach Mathematics in the first years of Elementary School for students with Autism Spectrum Disorder? Based on this guiding question, it was intended to study, identify, analyze and describe alternatives for educators to develop in their pedagogical practice in the early years in view of students with Autism Spectrum Disorder - ASD. To answer the proposed problem and achieve the objectives set, the research was developed in a qualitative approach, more specifically, the bibliographic research was adopted here. Through a contextualization of mathematics teaching in the early years and the specificities of Autism Spectrum Disorder, the present work portrayed some alternatives for learning the mathematical concepts seeking to establish if the strategy would be appropriate for autists. Thus, it was presented as a possibility for the diversification of the teacher's pedagogical practice the History of Mathematics, Problem Solving, Mathematical Modeling, Games, Information and Communication Technologies and Project-Based Learning. In order to establish whether each strategy would be viable for working with autistic students, we sought to interrelate the attributes of each and the characteristics of Autism Spectrum Disorder.